Epiphytes Modulate Posidonia oceanica Photosynthetic Production, Energetic Balance, Antioxidant Mechanisms, and Oxidative Damage - Costa, Monya M.; Barrote, Isabel; Silva, João; Olivé, Irene; Alexandre, Ana; Albano, Sílvia; Santos, Rui (Frontiers in Marine Science, 2015)
Epiphytes impose physical barriers to light penetration into seagrass leaves causing shading, which may decrease the production of oxygen reactive species (ROS), but also constitute a physical aggression that may trigger the production of ROS, leading to oxidative damage. Here we investigate the effects of epiphytes on Posidonia oceanica under both interactive perspectives, light attenuation and oxidative stress. Specifically the role of epiphytes in net photosynthesis, chlorophyll a and b, photoprotection (Violaxanthin+Anteraxanthin+Zeaxanthin cycle), soluble sugar and starch contents, enzymatic (ascorbate peroxidase (APX) and dehydroascorbate reductase (DHAR)) and global (trolox equivalent antioxidant capacity (TEAC)) and oxygen radical antioxidant capacity (ORAC)) antioxidant responses, phenolics and oxidative damage (malondialdehyde) are tested. Leaves with epiphytes showed higher chlorophyll b and lower content in VAZ cycle carotenoids. Epiphyte shading was the probable reason for the lower VAZ de-epoxidation-ratio of leaves with epiphytes. In spite of being shaded, leaves with epiphytes showed higher antioxidant levels, indicating that epiphytes trigger the production of ROS. Both ORAC and TEAC and also APX and DHAR activities were higher in leaves with epiphytes, indicating that this response was related with its presence. Malondialdehyde concentrations also suggest oxidative damage caused by epiphytes. We conclude that the epiphyte load causes oxidative stress in P. oceanica and the mechanisms to scavenge ROS were not completely effective to avoid cell damage.